Governance frameworks for COVID-19 research ethics review and oversight in Latin America: an exploratory study - Cabrera, Noelia (2021)
Fil: Cabrera, Noelia. CEDES. Centro de Estudios de Estado y Sociedad. Área de Salud, Economía y Sociedad; Argentina.